Inflammatory mediators in exhaled breath condensate of healthy donors and exacerbated COPD patients - Tateosian, Nancy Liliana (2012)
Samples of exhaled breath condensate (EBC) provide a convenient and non-invasive method to study inflammation in lung diseases. The aim of the present study was to evaluate and compare the inflammatory protein mediator levels in EBC from healthy donors (HD) and from patients with exacerbation of chronic obstructive pulmonary disease (COPD) using an EBC collection device with and without a coating of albumin as a carrier. We studied 13 HD and 26 patients with exacerbation of COPD. The concentrations of myeloperoxidase (MPO), IFNγ and secretory leukocyte protease inhibitor (SLPI) in EBC were measured by immunoassays. The EBC samples from HD and COPD patients showed higher concentrations of MPO when samples were recovered with an albumin-coated device. Furthermore, levels of MPO in COPD patients were significantly higher than in HD. An inverse correlation was observed between MPO and spirometric parameters (FVC and FEV1). Almost all samples collected with the albumin-coated device showed higher amounts of IFNγ and SLPI than those collected with the uncoated device. The levels of SLPI in COPD patients were significantly higher than in HD. A direct correlation was observed between FVC% predicted and SLPI. We concluded that coating the collection device with albumin increased the sensitivity of the technique, at least for measurements of MPO, SLPI and IFNγ. Furthermore, the higher levels of MPO and SLPI and lower levels of IFNγ in EBC from COPD patients could reflect the immunological status and the response of lung parenchyma to treatment during the exacerbation of the illness.